Forming the lowporous layers of indium phosphide with the predefined quality level - Vambol, Sergij; Bogdanov, Igor; Vambol, Viola; Suchikova, Yana; Kondratenko, Olexandr (Eastern-European Journal of Enterprise Technologies, 2018)
The morphological quality criterion was developed to have a possibility of formation of nanostructured layers on semiconductor surface with adjustable properties. The layers of low-porous indium phosphide with mesoporous structure were obtained. The porous layers were formed by the method of electrochemical etching in the solution of hydrochloric acid at constant current density. According to the developed criterion, the quality of synthesized por-InP samples was analyzed. This will make it possible to manufacture the structures with porous layers on the surface on an industrial scale. The presented criterion can be applied to other modes of treatment of indium phosphide or to other semiconductors. This will make it possible to treat it as a universal morphological criterion of quality of porous structures. The correlation between morphological properties of porous structures on the surface of indium phosphide and etching conditions was established. To do this, porous structures, which were formed in the interval of etching time from 10 to 20 min at different concentration of acid in the electrolyte, were analyzed. As a result, it was established that the shape of the pores of nanostructured layers on the surface of semiconductors depends not only on parameters of a crystal, but also on etching conditions, specifically, on etching time and electrolyte composition. The application of saturated electrolytes leads to formation of massive groove-shaped pores – elongated ellipses. The obtained correlations are useful from the practical point of view, as they make it possible to approach reasonably determining the modes of electrochemical treatment of semiconductors. In addition, it opens up new prospects in the construction of the model of self-organization of a porous structure on the surface of semiconductors. The technique of calculating basic statistical characteristics of the series of distribution of pores by dimensions, specifically, the variation span, dispersion, mean deviation, coefficients of variation and asymmetry was presented. This makes it possible to evaluate in detail the morphological indicators of porous structures and to progress in understanding the mechanisms behind the pore formation on the surface of semiconductors during electrochemical treatment.